ẢNH HƯỞNG CỦA THỨC ĂN, CHẾ ĐỘ CHO ĂN LÊN SINH TRƯỞNG VÀ TỶ LỆ SỐNG CỦA TU HÀI (Lutraria rhynchaena Jonas, 1844) GIAI ĐOẠN XUỐNG ĐÁY ĐẾN KÍCH CỠ 5mm - Phạm, Thị Thương Huyền; Ngô, Anh Tuấn; Phùng, Bảy; Nancy, Nevejan; Huỳnh, Đức Tâm (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
THE EFFECTS OF FOOD AND FOOD DIETS ON THE GROWTH AND SURVIVAL OF OTTER CLAM (LUTRARIA RHYNCHAENA, JONAS 1844) FROM SPAT STAGE TO JUVENILE OF 5 mm SIZEThis report presents the results of two studies on the effects of different algae species foods and food diets on the growth and survival rate of otter clam from the spat stage to 5mm- seed stage.The 5 algae species used to feed otter clam were Isochrysis galbana, Dicrateria sp, Chaetoceros calcitrans, Skeletonema costatum, Tetraselmis chuii. They were combined into four different trials, among them Tetraselmis chuii is used in all trials. The 36 day-trial result shows that the size and survival rate of otter clam in the trial done with Isochrysis galbana + Chaetoceros calcitrans + Tetraselmis chuii are the best (5.238 ± 2,22μm, 50,1 ± 1,46%).The otter clam spat was fed with four different food diets including (35.000; 40.000; 45.000; 50.000 cells/mL/day); (70.000; 80.000; 90.000; 100.000 cells/mL/day); (105.000; 120.000; 135.000; 150.000 cells/mL/day); (140.000; 160.000; 180.000; 200.000 cells/mL/day) at day periods respectively 1-7; 8-14; 15- 21; 22-5mm-seed. As a result, in the diet of 105.000; 120.000; 135.000; 150.000 cells/mL/da at 1-7; 8-14; 15-21; 22-36 days respectively, the size and survival rate of otter clam spat are the best (5.757± 5,7 μm, 51,1± 0,43%).